1989
DOI: 10.1016/0022-2828(89)90610-x
|View full text |Cite
|
Sign up to set email alerts
|

Urate production by human heart

Abstract: Xanthine oxidoreductase has been demonstrated in the heart of various species. However, its presence in human heart is still debated. In the literature, high to undetectable levels have been reported. We studied the arterial-venous mate difference across the heart of patients undergoing both routine cardiac catheterization and percutaneous transluminal coronary angioplasty. Urate is the end product of the reaction catalysed by xanthine oxidoreductase. In 10 patients, studied before angioplasty, the plasma mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 17 publications
3
15
1
Order By: Relevance
“…Measurement of serum UA can be repeatedly performed because it is simple, noninvasive, relatively inexpensive and routinely available. Interestingly, serum UA level in coronary sinus blood has been shown to increase following balloon inflation and to decrease following balloon deflation during coronary angioplasty, within a few minutes, 34 which does not conflict with the finding that in the present study serum UA level on admission in patients with acute PTE was already elevated soon after the onset of PTE. Thus, serum UA level may be used as a sensitive marker for the efficacy of treatment of PTE.…”
Section: Increased Serum Ua Level In Patients With Ptesupporting
confidence: 69%
“…Measurement of serum UA can be repeatedly performed because it is simple, noninvasive, relatively inexpensive and routinely available. Interestingly, serum UA level in coronary sinus blood has been shown to increase following balloon inflation and to decrease following balloon deflation during coronary angioplasty, within a few minutes, 34 which does not conflict with the finding that in the present study serum UA level on admission in patients with acute PTE was already elevated soon after the onset of PTE. Thus, serum UA level may be used as a sensitive marker for the efficacy of treatment of PTE.…”
Section: Increased Serum Ua Level In Patients With Ptesupporting
confidence: 69%
“…After ischemia, the human heart releases hypoxanthine due to A T P catabolism [14,18,[28][29][30]. In contrast to earlier work [14,30], coronary occlusion did not influence venous hypoxanthine.…”
Section: Oxgpurine M E T a B O L I S Mcontrasting
confidence: 59%
“…The appearance of urate indicates that human heart contains some xanthine oxidoreductase activity [29]. On the other hand, perfusion of explanted human hearts with hypoxanthine gives rise to negligible urate production [32].…”
Section: Oxgpurine M E T a B O L I S Mmentioning
confidence: 99%
“…Regional ischaemia, such as that produced during coronary angioplasty [67] or tourniquet exsanguination of the forearm [68] also produces elevations in serum uric acid. We have previously shown that in chronic heart failure, serum uric acid is inversely related to maximal oxygen consumption during a maximal treadmill exercise test [1] and to maximal leg blood flow [69] .…”
Section: Discussionmentioning
confidence: 99%